Physiology of spontaneous [Ca2+]i oscillations in the isolated vasopressin and oxytocin neurones of the rat supraoptic nucleus. Issue 6 (June 2016) - Kortus, Stepan; Srinivasan, Chinnapaiyan; Forostyak, Oksana; Ueta, Yoichi; Sykova, Eva; Chvatal, Alexandr; Zapotocky, Martin; Verkhratsky, Alexei; Dayanithi, Govindan
Graphical abstract: Trace (A) shows a typical transient [Ca 2+ ]i response induced by 50 mM K + observed in an AVP-eGFP neurone (inset), Trace (B) shows the spontaneous [Ca 2+ ]i oscillations observed in an AVP-eGFP neurone (inset). The corresponding changes in the fluorescence are shown in C and D, respectively. Highlights: Supraoptic fluorescent vasopressin (AVP-eGFP) and oxytocin (OT-mRFP1) neurones exhibit distinct spontaneous [Ca 2+ ]i oscillations. Vasopressin triggers [Ca 2+ ]i oscillations, intensifies existing oscillations, and exceptionally stops oscillations. Hyper- or hypo-osmotic stimuli have an intensifying or inhibitory effect on oscillations, respectively. Nearly 90% of neurones from 3 or 5-day-dehydrated rats exhibit oscillations. More than 80% of OT-mRFP1 neurones from 3 to 6-day-lactating rats are oscillatory vs . about 44% in virgins. Abstract: The magnocellular vasopressin (AVP) and oxytocin (OT) neurones exhibit specific electrophysiological behaviour, synthesise AVP and OT peptides and secrete them into the neurohypophysial system in response to various physiological stimulations. The activity of these neurones is regulated by the very same peptides released either somato-dendritically or when applied to supraoptic nucleus (SON) preparations in vitro . The AVP and OT, secreted somato-dendritically ( i.e. in the SON proper) act through specific autoreceptors, induce distinct Ca 2+ signals and regulate cellular events. Here, we demonstrate that about 70% of freshly isolated individual SON neurones from the adult non-transgenic or transgenic rats bearing AVP (AVP-eGFP) or OT (OT-mRFP1) markers, produce distinct spontaneous [Ca 2+ ]i oscillations. In the neurones identified (through specific fluorescence), about 80% of AVP neurones and about 60% of OT neurones exhibited these oscillations. Exposure to AVP triggered [Ca 2+ ]i oscillations in silent AVP neurones, or modified the oscillatory pattern in spontaneously active cells. Hyper- and hypo-osmotic stimuli (325 or 275 mOsmol/l) respectively intensified or inhibited spontaneous [Ca 2+ ]i dynamics. In rats dehydrated for 3 or 5 days almost 90% of neurones displayed spontaneous [Ca 2+ ]i oscillations. More than 80% of OT-mRFP1 neurones from 3 to 6-day-lactating rats were oscillatory vs . about 44% (OT-mRFP1 neurones) in virgins. Together, these results unveil for the first time that both AVP and OT neurones maintain, via Ca 2+ signals, their remarkable intrinsic in vivo physiological properties in an isolated condition.